2022
DOI: 10.3390/c8010009
|View full text |Cite
|
Sign up to set email alerts
|

From Waste Plastics to Carbon Nanotube Audio Cables

Abstract: Carbon nanotubes (CNTs) have long been at the forefront of materials research, with applications ranging from composites for increased tensile strength in construction and sports equipment to transistor switches and solar cell electrodes in energy applications. There remains untapped potential still when it comes to energy and data transmission, with our group having previously demonstrated a working ethernet cable composed of CNT fibers. Material composition, electrical resistance, and electrical capacitance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The peak at ~ 1350 cm −1 confirms a disorder D-peak which is attributed primarily to amorphous carbon [29,31], whereas the taller G-peak at ~ 1600 cm −1 is attributed to graphitic carbon, which in this case would be the CNTs themselves. The presence of a strong G' peak at ~ 2650 cm −1 combined with an I G /I D of under 1 is also indicative of multi-walled CNTs in the product, which is in line with previous work [23,24]. Likewise, we do not see radial breathing modes at 785 nm, as seen in Fig.…”
Section: Cnt Characterizationsupporting
confidence: 93%
See 2 more Smart Citations
“…The peak at ~ 1350 cm −1 confirms a disorder D-peak which is attributed primarily to amorphous carbon [29,31], whereas the taller G-peak at ~ 1600 cm −1 is attributed to graphitic carbon, which in this case would be the CNTs themselves. The presence of a strong G' peak at ~ 2650 cm −1 combined with an I G /I D of under 1 is also indicative of multi-walled CNTs in the product, which is in line with previous work [23,24]. Likewise, we do not see radial breathing modes at 785 nm, as seen in Fig.…”
Section: Cnt Characterizationsupporting
confidence: 93%
“…CNT product, as powder, was used to manufacture individual wires as described before [23,24]. In short, the CNTs were firmly packed into the sheath of heat shrink tubing and copper wire was inserted into either end followed by compression for increased CNT-Cu contact.…”
Section: Preparation and Testing The Cnt Ethernet Cablementioning
confidence: 99%
See 1 more Smart Citation
“…It is the most frequently used approach to fabricate high-quality CNTs from plastics, and is suitable for continuous fabrication, but the carbon yield is usually below 20%. Gangoli et al 2022 ; Jia et al 2022 ; Liu et al 2011 ; Tripathi et al 2017 ; Xu et al 2021b ; Yang et al 2018 ; Yao et al 2018b , Yao et al 2017 ; Zhuo et al 2010 Microwave Microwave is a rapid heating method and can effectively transform different plastics into hydrogen and CNTs in 30–90 seconds. The yields of carbon and hydrogen obtained from the microwave method can achieve 80% and 97%, respectively.…”
Section: Morphology Control Of Carbonaceous Materialsmentioning
confidence: 99%
“…e ndings of this study were expected to improve the design of nanomechanical CNT-based devices that carry uid under various conditions. Gangoli et al, employing the nite element approach, suggested to investigate the coupled impacts of surface features and nonlocal elasticity on nanobeam vibration characteristics [34]. Furthermore, the ability of the nite element method to handle a complex geometry was demonstrated.…”
mentioning
confidence: 99%